Meson spectral functions with chirally symmetric lattice fermions - Gert Aarts (Journal of High Energy Physics, 2006)
In order to enhance our understanding of spectral functions in lattice QCD obtained with the help of the Maximum Entropy Method, we study meson spectral functions for lattice fermions with chiral symmetry. In particular we analyse lattice artefacts for standard overlap, overlap hypercube and domain wall fermions in the free field limit. We also present first results for pseudoscalar spectral functions in dynamical QCD with 2+1 flavours of domain wall fermions, using data generated by the UKQCD and RBC collaborations on QCDOC machines.